Health promoting schools: a multicomponent program to prevent behavioral risks amongst adolescents (2014-2017) - Peñaherrera , Edwin (2020)
DOI: 10.26439/persona2020.n023(1).4834 This article is based on the analysis of the systematization of the Health Promoting School project implemented in Lima, Peru, from 2014 to 2017 by an agreement between the International cooperation agency of South Korea and the Ministry of health in Peru. A description of the phases developed, the strategies used, and the alliances built for their implementation will be presented. For that purpose, a review of secondary sources and interviews to key players as primary sources were made. The project considered the prevention and health promotion paradigms as complementary ones.